Immigration, Public Education Spending, and Private Schooling - Mavisakalyan, Astghik (Southern Economic Association, 2011)
This article examines the impact of immigration on private school enrollment through themechanism of public education spending. It fmds that the immigrant share of populationraises private school enrollment across countries by leading to a decrease in the share ofpublic education spending. The decrease is driven by responses to immigrants fromculturally similar and developed countries. This suggests that the role of public schools inpromoting social cohesion among diverse populations is weighted against other concernsin education funding decisions in places with immigrant populations. The endogeneity ofimmigrant share is accounted for by using an instrument constructed from gravity modelestimates.